ANALISIS EKONOMI POLITIK DI ARAS LOKAL (STUDI PENGELOLAAN BADAN USAHA MILIK DESA DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DESA IMBANAGARA RAYA) - Asep Nurwanda; Elis Badriah; Anis Lisara (Bajang Institute, 2021)
The study is titled, Political Economy at The Local With Studies about management village-owned business entity (BUMDES) in order to improve the welfare of the Imbanagara Raya village community, Ciamis Regency. The purpose of this study was to find out how the management of the Imbanagara Raya Village Owned business entity in improving community welfare. The theory used by researchers is political economy. Neoclassical politic economy specifically state centred approach. The research method used a qualitative research method with the technique of determining informants, namely by purposive sampling with data collection through interviews, observation and documentation, then the data obtained is reduced to be selected according to the needs for further collection and then concluded to be presented. The results of the study show that the management of the Imbanagara Raya Village-Owned Enterprises (BUMDes) has not gone well. This can be seen from the types of businesses that have been built have not progressed. Although Imbanagara Raya Village-Owned Enterprises (BUMDes) have not had a positive impact on the entire Imbanagara Raya Village society in improving the village economy and the welfare of the Imbanagara Raya Village society. But with the existence of BUMDes at least it can benefit by being able to provide input to the APBDes.